Utilizing Mobile Technology in Enhancing Teaching and Learning in Mathematics - Hagos, Luisito C.; Delos Santos, Alejandro D.; Lim, Ulysis V. (INTI University College, 2009)
Because of the fast paced technology, the academe is already becoming technology-enriched more so in the delivery of instruction. The teaching and learning can now be executed through modem means of instructions - eLearning, d.learning and m.learning (mobile learning). The objective of this research was to enhance teaming through the use of text messaging or short message system (SMS) In Mathematics particularly in Algebra, Trigonometry and Calculus. in spite of very Limited characters In the SMS the Lectures developed included sample problems equipped with schematic diagram (figure), formula and solution. The researchers developed mathematics Lectures in SMS format and aimed to find out the engineering students’ assessment of the lecture-texts. The research found out that the lecture-texts are valuable tool in filling in the students’ time into (earning opportunities specialty when teachers are late or absent from class. The research also found out the students assessed the lecture-texts’ illustrations. Contents, ability to promote self-learning, ease of use, self-pacing and f flexibility as very satisfactory.